Temporal Trends in Diagnosis, Treatments, and Outcomes in Patients With Bicuspid Aortic Valve - Kim, Kyu; Kim, Dae-Young; Seo, Jiwon; Cho, Iksung; Hong, Geu-Ru; Ha, Jong-Won; Shim, Chi Young (Frontiers in Cardiovascular Medicine, 2021)
BACKGROUND: The population is aging and advances in multimodal imaging and transcatheter valve intervention have been prominent in the past two decades. This study investigated temporal trends in demographic characteristics, use of multimodal imaging, treatments, and outcomes in patients with bicuspid aortic valve (BAV). METHODS AND RESULTS: A total of 1,497 patients (male 71.7%, 57±14 years old) first diagnosed with BAV between January 2003 and December 2020, in a single tertiary center were divided into three groups according to year of diagnosis: group 1 (2003-2008, n=269), group 2 (2009-2014, n=594), and group 3 (2015-2020, n=634). The patients’ demographic characteristics, comorbidities, BAV morphology, BAV function, BAV-related disease, use of multimodal diagnostic imaging, treatment modality for BAV, and clinical outcomes were compared among the three groups. The ages at diagnosis and at the time of surgery/intervention increased considerably from group 1 to 3. The patients’ comorbidity index also increased progressively. The proportion of non-dysfunctional BAV and significant AS increased, while that of significant AR decreased. The frequency of infective endocarditis as an initial presentation significantly decreased over time. Additionally, the use of multimodal imaging increased markedly in the most recent group. The results also indicated increasing trends in the use of bioprosthetic valves and transcatheter aortic valve replacement. Overall and cardiovascular survival rates improved from group 1 to 3 (log rank p<0.001). CONCLUSIONS: For the past two decades, remarkable temporal changes have occurred in patient characteristics, use of multimodal diagnostic imaging, choice of treatment modality, and clinical outcomes in patients with BAV.